Sensus Fidei, Sesus Fidelium and the Magisterium - George Kochuthara, Shaji (Asian Horizons, 2018)
The whole body of the faithful who have an anointing that comes from the holy one (cf. 1 Jn.2:20 and 27) cannot err in matters of belief. This characteristic is shown in the supernatural appreciation of the faith (sensus fidei) of the whole people, when, “from the bishops to the last of the faithful” they manifest a universal consent in matters of faith and morals (Vatican II, LG, 12). The Second Vatican Council affirmed that the body of the faithful as a whole, as they are anointed by the Holy Spirit, have a supernatural sense of faith (sensus fidei) which has an unerring quality, when there is a universal agreement among them in matters of ‘faith and morals.’ This sense of faith of the community is discerned and articulated by the official teaching authority of the Church whenever it is called for (LG, 12, DV, 10).